Xanthohumol Prevents Atherosclerosis by Reducing Arterial Cholesterol Content via CETP and Apolipoprotein E in CETP-Transgenic Mice - Hirata, Hiroshi (Public Library of Science, 2012)
BACKGROUND: Xanthohumol is expected to be a potent anti-atherosclerotic agent due to its inhibition of cholesteryl ester transfer protein (CETP). In this study, we hypothesized that xanthohumol prevents atherosclerosis in vivo and used CETP-transgenic mice (CETP-Tg mice) to evaluate xanthohumol as a functional agent. METHODOLOGY/PRINCIPAL FINDINGS: Two strains of mice, CETP-Tg and C57BL/6N (wild-type), were fed a high cholesterol diet with or without 0.05% (w/w) xanthohumol ad libitum for 18 weeks. In CETP-Tg mice, xanthohumol significantly decreased accumulated cholesterol in the aortic arch and increased HDL cholesterol (HDL-C) when compared to the control group (without xanthohumol). Xanthohumol had no significant effect in wild-type mice. CETP activity was significantly decreased after xanthohumol addition in CETP-Tg mice compared with the control group and it inversely correlated with HDL-C (%) (P<0.05). Furthermore, apolipoprotein E (apoE) was enriched in serum and the HDL-fraction in CETP-Tg mice after xanthohumol addition, suggesting that xanthohumol ameliorates reverse cholesterol transport via apoE-rich HDL resulting from CETP inhibition. CONCLUSIONS: Our results suggest xanthohumol prevents cholesterol accumulation in atherogenic regions by HDL-C metabolism via CETP inhibition leading to apoE enhancement.